Politeness and Impoliteness Strategies in Sundanese Language Podcasts on the YouTube Channel Ridwan Remin - Islami, Hasna Nur; Sudana, Dadang; Wawan Gunawan (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research examines politeness and impoliteness strategies in the Sundanese language as used on the Ridwan Remin YouTube podcast. Analyzing these strategies provides insights into cultural and social norms, enhances understanding of interpersonal communication within the Sundanese community, and demonstrates how traditional linguistic practices evolve in modern media contexts. As podcast media gains popularity, studying these strategies in this digital format reveals how traditional practices adapt to reflect broader social and cultural changes. This qualitative study utilizes politeness theory by Brown & Levinson (1987) and impoliteness theory by Culpeper (1996), alongside pragmatics, to explore how speakers manage social relationships through language in a podcast setting. The research focuses on the podcast episode